1271. HIV-1 Drug Resistance in Patients Failing Integrase Strand Transfer Inhibitor-Based Regimens in Rhode Island, USA. (15th December 2022) - Nagel, Katherine E; Novitsky, Vladimir; Aung, Su; Solomon, Matthew; Won, Cindy; Brotherton, Amy; Howison, Mark; Gillani, Fizza S; Kantor, Rami
Abstract: Background: Integrase Strand Transfer Inhibitors (INSTIs) are the most common antiretroviral therapy (ART) anchor drugs. Despite reassuring clinical trial data, real-life extent and characteristics of resistance at failure of INSTI-based regimens are unclear and can inform care. Methods: We investigated drug resistance upon failure of INSTI-based regimens at the largest HIV program in Rhode Island (RI), caring for > 80% of the state's people with HIV. Eligible patients had full ART history, were on INSTI-based regimens, and had available protease-reverse transcriptase-integrase sequences from clinical care. Resistance interpretation was done with Stanford Database tools. Results: Of 1, 169 eligible patients (55% of clinic population), 102 (9%) were failing INSTI-based regimens; mean age at genotyping 39 years, CD4 377 cells/µL, and 11 years on ART; 67% male; 53% white, 44% Black, 63% non-Hispanic; 58% US born; with prior exposure to 8 drugs and 4 regimens. Of these 102, 55% were on 1 st -generation INSTI (41% elvitegravir (EVG); 14% raltegravir (RAL)), and 45% on 2 nd -generation INSTI (23% bictegravir (BIC); 22% dolutegravir (DTG)); most (73%) with only 2 NRTIs. Overall, 57% had any intermediate-high level predicted resistance (55% on 1 st -, 45% on 2 nd -generation INSTI); NRTI 37%; NNRTI 40%; PI 3%; INSTI 22% (EVG 22%, RAL 21%, DTG/BIC/cabotegravir 8% each). Common INSTI mutations were N155H (n=7); E92Q, Q148H/R, S147G (5 each); T66I/K, E138A/K/T (4 each); G140A/S (3), R263K (2), Y143R (1). Multi (≥ 3) class resistance occurred in 12%, a third of whom had intermediate-high resistance to all five INSTIs (50% on 1 st -, 50% on 2 nd -generation). Resistance trends were stable over 2014-2021, and 2 nd -generation INSTI resistance was only seen in those with prior exposure to 1 st -generation INSTI. Conclusion: At the largest RI HIV clinic, 9% of eligible patients were failing INSTI-based regimens, most with clinically relevant resistance that was stable over time, and 1% had multi-class resistance including some to all available INSTIs. Though low resistance levels to 2 nd -generation INSTIs are encouraging, they exist; and continued ADR monitoring is important, particularly with increasing incorporation of INSTIs in HIV treatment and prevention and use of 2-drug regimens. Disclosures: All Authors : No reported disclosures.